PENGARUH KOMPOS LIMBAH KACANG PANJANG TERHADAP PRODUKSI TANAMAN JAGUNG MANIS (ZEA MAYS L. SACCHARATA) - Ismail Efendi; Imran Muliadi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
This research uses organic fertilizer that is compost of long bean plant waste applied to sweet corn plant (Zea mays L. saccharata). The purpose of this research is to know the influence of compost of long bean plant waste with different dose to sweet corn production and to know the optimal dose to get the maximum production of sweet corn. The study used a single randomized Randomized Design (RAL) with 4 treatment factors: dose 0 g / plant (D0), 125 g / plant (D1), 250 g / plant (D2) and 375 gr / plant (D3). The data obtained were analyzed by Anova followed by Duncan's Multiple Range Test (DMRT) at 5% significance level. The results showed that the production on treatment D1, D2 and D3 was lower than D0.